2003
DOI: 10.1007/s00105-003-0554-x
|View full text |Cite
|
Sign up to set email alerts
|

pH-Wert des Milieus chronischer Wunden

Abstract: The pH value of chronic wounds influences directly or indirectly many factors important to wound healing. We measured 247 pH values in 39 patients with chronic wounds of varying origins, detecting values from 5.45 to 8.65. Over a period of 12 months, individual values varied up to 1.73 units. Knowledge of pH values helps insure an adequate chronic wound therapy. For example, many enzymatic wound products have pH values outside the above values. Our results also show that the pH value is a dynamic factor which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(55 citation statements)
references
References 20 publications
1
49
0
5
Order By: Relevance
“…Hence, establishing a low physiological pH might aid wound healing [27]. Chemical acidification of the wound bed is thought to reduce bioburden as the growth of most human pathogens is inhibited at pH levels <6.0 [17]. This could be confirmed by tests using MLN where acidic pH led to a significant decrease of bacterial growth.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Hence, establishing a low physiological pH might aid wound healing [27]. Chemical acidification of the wound bed is thought to reduce bioburden as the growth of most human pathogens is inhibited at pH levels <6.0 [17]. This could be confirmed by tests using MLN where acidic pH led to a significant decrease of bacterial growth.…”
Section: Discussionsupporting
confidence: 51%
“…The pH milieu in wounds has a direct as well as an indirect influence on many factors during wound healing. Studies have shown that the pH of chronic wounds most commonly has a range of 6.5-8.5 while the pH of acute, healing wounds is significantly lower [16,17]. This alkalization or ‘alkaline shift' is thought to be due to tissue necrosis and the presence of microorganisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…it may reduce the pH of the culture media from 7 to less than 4 [50]. Acidification of the environment can inhibit microbial growth efficiently [51]. The analysis of how CAP treatment affects different culture media is the focus of an ongoing study.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we aimed to develop microparticulate system for controlled release of antimicrobial agent in the alkaline media as open wounds tend to have a neutral or alkaline pH, predominantly in the range of 6.5-8.5. 16) In the present investigation, the effect of Glycerol (X 1 ) and NaCl (X 2 ) concentration in outer aqueous phase was selected as independent variables while the entrapment efficiency (Y 1 ), particle size (Y 2 ) and % yield (Y 3 ) were chosen as the dependent variables. The levels for these two parameters were determined from the preliminary trials.…”
mentioning
confidence: 99%